Science, Religion, and Italy's Seventeenth-Century Decline: From Francesco De Sanctis to Benedetto Croce - Tarrant, Neil (Zygon, 2019)
Historians have often argued that from the mid-sixteenth century onward Italian science began to decline. This development is often attributed to the actions of the so-called Counter-Reformation Church, which had grown increasingly intolerant of novel ideas. In this article, I argue that this interpretation of the history of science is derived from an Italian liberal historiographical tradition, which linked the history of Italian philosophy to the development of the modern Italian state. I suggest that although historians of science have appropriated parts of this distinctive narrative to underpin their account of Italy's seventeenth-century scientific decline, they have not always fully appreciated its complexity. In this article, I consider the work of two scholars, Francesco de Sanctis and Benedetto Croce. Both explicitly suggested that although the actions of the Church caused Italy to enter into a period of decline, they in fact argued that science represented one of the few areas in which Italian intellectual life actually continued to thrive.